2016
DOI: 10.13073/fpj-d-15-00070
|View full text |Cite
|
Sign up to set email alerts
|

Within-Tree and Tree-Age Variation of Selected Anatomical Properties of the Wood of Ugandan-Grown Eucalyptus grandis

Abstract: The challenges of utilizing Eucalyptus grandis thinnings prompted a study into its anatomical properties with the aim of identifying its potential based on the within-tree axial and tree-age variation. Fiber length, fiber diameter, vessel length, vessel diameter, vessel average, ray height, and ray frequency at 3, 6, 9, and 12 years were studied. Axial sample portions at 25, 50, and 75 percent of tree height were collected from western Uganda and prepared for maceration, microtomy, and microscopy. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Relatively stable fibre lumen diameter values with cambial age and axial height suggested this mechanical trait was not affected by these two factors, in comparison with vessel-related and thus hydraulic traits. However, decreased fibre length and latewood fibre wall thickness to diameter ratio with axial height agrees with a former study [67], and might be associated with declined xylem water potential to the crown and thus the vertical drop in cell turgor pressure. This demonstrates that the cell turgor gradient affects cell elongations during cell differentiation, although the gradient might be rather small [68][69][70][71].…”
Section: Vertical and Radial Patterns Of Wood Anatomical Traitssupporting
confidence: 91%
“…Relatively stable fibre lumen diameter values with cambial age and axial height suggested this mechanical trait was not affected by these two factors, in comparison with vessel-related and thus hydraulic traits. However, decreased fibre length and latewood fibre wall thickness to diameter ratio with axial height agrees with a former study [67], and might be associated with declined xylem water potential to the crown and thus the vertical drop in cell turgor pressure. This demonstrates that the cell turgor gradient affects cell elongations during cell differentiation, although the gradient might be rather small [68][69][70][71].…”
Section: Vertical and Radial Patterns Of Wood Anatomical Traitssupporting
confidence: 91%
“…The same result was reported by Tavares et al (2011), Taylor (1973), and Zobel and Buijtenen (1989), where the fiber length was essentially the same at all heights and was not influenced by height. Sseremba et al (2016) reported that fiber length decreased from the base to the top of the tree.…”
Section: Fiber and Vessel Element Lengthmentioning
confidence: 99%
“…In fact, plantation grown Eucalyptus is currently the top of the previously lesser utilised species preferred for manufacturing a variety of products such as furniture, wood cabinets and house roofing. It has a high biomass accumulation rate resulting into a maturity span between 6-12 years depending on the end-use however, the average harvesting time for most construction works is 10 years (Sseremba et al, 2016).…”
Section: Introductionmentioning
confidence: 99%